Avaliação do perfil dos pacientes que permanecem na sala de recuperação pós-anestésica de um hospital terciário de emergência - Ferreira, Luciano Paulo (2016)
This study evaluated the patients in the Post Anesthetic Recovery Room of the Institute Dr. José Frota during the months of January and February 2016. The aim of this study is to assess the epidemiological profile of hospitalized patients in the post-anesthetic recovery room a tertiary care hospital of Emergênca. The specific objectives consist in Evaluating a sample of patients who remained beyond two hours in the Post-Anesthetic Care Unit (PACU) Dr. José Frota Institute (IJF), as concerns: the epidemiological profile; The cause of the occurrence; The anatomical tracking of the affected body; The origin of the patients; Assistance by applying the Aldrete and Kroulik scale; The day of the week there was a higher rate sojourn; The cause of the long stay in the PACU. The present epidemiological cross-sectional study was designed to be descriptive nature with quantitative approach. The survey was conducted in the Post-Anesthetic Care Unit of Dr. José Frota Institute Fortaleza, State of Ceara. It was observed that the patients who had stay beyond two hours at room hours in the Post-Anesthetic Care Unit (PACU) Dr. José Frota Institute (IJF) had the following characteristics: predominantly were young men; It is the main cause of the occurrence that resulted in surgery and the need for long stay in the PACU was motorcycle accident; anatomical following the most commonly affected body was the skull, followed by the lower limbs; the provenance of the patients were predominantly of Fortaleza capital; assistance in the PACU by applying the Aldrete and Kroulik scale was virtually non-existent; the day of the week that there was a greater long permancência rate of patients was Monday; the main causes of long-term absence was vacant beds in the ward and absence of vacant beds in the Intensive Care Unit. We conclude that patients presenting stay beyond two hours at room hours in the Post-Anesthetic Care Unit (PACU) Dr. José Frota Institute (IJF) had the following characteristics: predominantly were young men; The main cause of the occurrence that resulted in surgery and the need for long stay in the PACU was motorcycle accident; Anatomic following the most commonly affected body was the skull, followed by the lower limbs; The provenance of the patients were predominantly of Fortaleza capital; Assistance in the PACU by applying the Aldrete and Kroulik scale was virtually non-existent; the day of the week that there was a greater long permancência rate of patients was Monday; The main causes of long-term absence was vacant beds in the ward and absence of vacant beds in the Intensive Care Unit. Keywords: Hospitals, packaged. Wounds and injuries. Surgery. Recovery room. Patient discharge.